Pelatihan Pengolahan Bingke’ berbahan Eucheuma cottonii pada Mahasiswa dan Alumni Ilmu Kelautan Universitas Tanjungpura - minsas, sukal; warsidah; Nurdiansyah , Syarif Irwan; Helena, Shifa (Lembaga Dongan Dosen, 2023)
Bingke' is a typical Pontianak food made from eggs, coconut milk, granulated sugar and wheat flour. Some of the existing flavor variants include pumpkin, potato, taro and corn, which apart from providing a new taste, are also a partial substitute for wheat flour. The aim of this PKM activity is to improve the skills and understanding of activity participants, namely marine science students and alumni, in processing fishery products into bingke' as a high-fiber food preparation, as well as developing a business utilizing E. cottonii seaweed, which is one of the one of the leading fisheries commodities in West Kalimantan. The activity was attended by 18 participants consisting of 9 students and 9 alumni of the Department of Marine Science, Tanjungpura University. From the evaluation results during the activity until the end, it shows that the training participants already have the knowledge and skills in making seaweed-based bingke, with a savory and delicious taste and a distinctive seaweed aroma and a medium consistency, not hard and not too soft.